Elementary Fitness for Life in Action. (2nd September 2016) - Phelps, Ashley Nicole; McLeod, Candice; Hodges-Kulinna, Pamela; Lorenz, Kent; Stylianou, Michalis
Abstract : The Institute of Medicine and SHAPE America, among other national and international organizations, are promoting comprehensive school physical activity programs or whole-of-school approaches to creating healthy and active schools. The purpose of this article is to briefly describe what a comprehensive school physical activity program (CSPAP) is, as well as the concept of wellness weeks to increase student's physical activity during the school day. It also provides three examples of classroom projects that support CSPAP and wellness week activities in schools.